Composite diaphragm for semi-solid battery and preparation method of composite diaphragm
By using ABA three-layer composite separator in semi-solid state batteries, using Zn-MOF derived carbon materials and polypropylene materials, the problems of high internal resistance and poor interface stability of solid state batteries are solved, and higher energy density and safety are achieved sex.
Patent Information
- Application Number
- CN202411985906.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The high internal resistance, poor interface stability and high manufacturing costs of existing solid-state batteries limit their large-scale application. As a transition technology, the importance and application challenges of separators in it are particularly prominent.
A three-layer composite separator is used, Zn-MOF derived carbon material and polyethylene oxide (PEO) of layer A, and polypropylene material of layer B, and three-layer coextrusion and heat treatment are used to improve the ionic conductivity of the separator and Mechanical properties.
It improves the energy density and safety of the battery, reduces the use of liquid electrolytes, enhances the puncture and tensile strength of the diaphragm, and improves the overall performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery diaphragms, and in particular to a composite diaphragm for a semi-solid battery and a preparation method thereof. Background Art
[0002] Since the ionic conductivity of most solid electrolytes is lower than that of liquid electrolytes, this may lead to a higher internal resistance of the battery, affecting its power density. At the same time, the interface stability between the solid electrolyte and the electrode material is a challenge, and the interface impedance may lead to a decrease in battery performance. In addition, the processing technology of solid electrolytes and electrodes is not yet mature, and the manufacturing process may be complicated and costly, which limits the large-scale application of solid-state batteries. Before major breakthroughs are made in the interface problems and manufacturing costs of solid-state batteries, semi-solid batteries are the only way to go at this stage, and are also the optimal solution under the current environment under comprehensive cost and market selection factors.
[0003] As a semi-solid battery that has not completely abandoned liquid electrolytes, the separator plays an important role in semi-solid batteries and is an important component. Solid polymer electrolyte (SPE), also known as ion-conducting polymer. The research on solid polymer electrolytes began in 1973 with the discovery of the conductivity of polyethylene oxide (PEO) and alkali metal ion complexes by Wright et al. In 1979, Armand et al. in France reported that the ionic conductivity of PEO alkali metal salt complexes reached 10 at 40-60°C. -5 S / cm, and has good film-forming properties, and can be used as lithium-ion battery electrolytes. Replacing traditional liquid electrolytes with solid electrolytes is expected to fundamentally solve the safety problems of batteries. However, solid electrolytes still have problems such as low mechanical strength and poor wettability, which limit their application in separators. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a composite diaphragm for a semi-solid battery and a preparation method thereof. The diaphragm adopts an ABA three-layer structure. The A layer adopts Zn-MOF-derived carbon material and polyethylene oxide, which can synergistically improve the ionic conductivity of the electrolyte. The use of polymer solid electrolyte can also reduce the use of liquid electrolyte, further improving battery safety; the B layer adopts polypropylene material, which can give the diaphragm strong mechanical properties, so that the overall composite diaphragm has sufficient puncture strength and tensile strength, thereby obtaining a composite diaphragm with better overall performance.
[0005] The purpose of the present invention is achieved through the following technical solutions: In the first aspect, the present invention provides a composite diaphragm for a semi-solid battery, comprising an ABA three-layer structure obtained by co-extrusion of three layers; the raw material of layer B comprises polypropylene; in terms of mass percentage, the raw material of layer A is 85-95% PEO, 0-5% Zn-MOF material and the remaining Zn-MOF-derived carbon material; the Zn-MOF-derived carbon material is obtained by calcining the Zn-MOF material at 900-1200°C in an inert atmosphere for 3-6 hours.
[0006] The composite diaphragm in the present invention is an ABA three-layer structure, and the A layer (upper and lower surface layers) uses Zn-MOF derived carbon material and polyethylene oxide (PEO). PEO is a polymer solid electrolyte, which can reduce the use of liquid electrolyte and improve the overall energy density of the battery. Zn-MOF derived carbon material is obtained by high-temperature oxygen-free calcination of Zn-MOF material, and the Zn element in the framework can be removed, and only the MOF skeleton structure is retained. It can also avoid the risk of MOF composed of redox elements (Zn) being degraded near the electrode interface, and the MOF skeleton after calcination will have defective structures due to the vaporization and escape of Zn, so it will provide more active sites in the entire electrochemical process, greatly shorten the ion transport path, and promote the electrochemical reaction. At the same time, mixing Zn-MOF derived carbon material with PEO can prevent PEO recombination, reduce its crystal phase ratio, improve PEO chain movement, and improve the ionic conductivity of the electrolyte.
[0007] In addition, the raw materials of layer A (upper and lower surface layers) can also be Zn-MOF derived carbon materials, Zn-MOF materials and polyethylene oxide (PEO). Adding a certain amount of Zn-MOF materials can cooperate with Zn-MOF derived carbon materials. Zn-MOF and derived carbon material particles are distributed in the PEO matrix as cross-linking centers, which can prevent PEO recombination. However, when the amount of Zn-MOF material added is too much, even if Zn-MOF derived carbon materials are added, it is not possible to effectively reduce the redox problems of Zn-MOF materials in the reaction process and the impact of disintegration problems in long-term charging and discharging, which leads to a low capacity retention rate of the battery.
[0008] The B layer is made of polypropylene material. The properties of polypropylene material itself give the diaphragm strong mechanical properties, so that the overall composite diaphragm has sufficient puncture strength and tensile strength, and has sufficient safety factor when conducting battery tests. At the same time, the use of polypropylene material with a low melt index can reduce the thickness of the overall diaphragm as much as possible while ensuring mechanical strength, which is conducive to lightweighting of the battery.
[0009] The present invention, through the structural design of the diaphragm and the ratio of raw materials, introduces a polymer solid electrolyte in the form of a film layer to co-extrude with the base film, while ensuring that the mechanical strength of the diaphragm is sufficient. This alleviates the phenomenon of paint shedding that is easy to occur when the solid electrolyte is coated on the membrane surface to a certain extent. In addition, the use of the polymer solid electrolyte can improve the energy density of the battery and reduce the use of liquid electrolyte, further improving the safety of the battery.
[0010] Preferably, in the ABA three-layer structure, the thickness ratio of the A layer, the B layer and the A layer is 10-20%: 60-80%: 10-20%, and the thickness of the upper and lower A layers is the same. More preferably, in the ABA three-layer structure, the thickness ratio of the A layer, the B layer and the A layer is 10-15%: 70-80%: 10-15%, and the thickness of the upper and lower A layers is the same.
[0011] Preferably, the composite membrane has a thickness of 12-20 μm.
[0012] Preferably, the melt index of the polypropylene is 0.8-1.0 g / 10 min.
[0013] Preferably, the mass percentage of the added Zn-MOF material is not greater than the mass percentage of the added Zn-MOF derived carbon material.
[0014] Preferably, the heating rate during calcination is 10-15°C / min.
[0015] Preferably, the inert atmosphere is nitrogen and / or argon atmosphere.
[0016] In a second aspect, the present invention provides a method for preparing a composite diaphragm for a semi-solid battery, comprising the following steps: (1) In an inert atmosphere, calcining the Zn-MOF material at 900-1200°C for 3-6 hours to obtain a Zn-MOF-derived carbon material; (2) The raw materials of layer A and layer B are mixed in proportion, and then subjected to three-layer co-extrusion, cooling and pulling to obtain a cast sheet; (3) The cast sheet is subjected to heat treatment, longitudinal cold stretching, longitudinal hot stretching, and heat setting in sequence to obtain a composite separator for a semi-solid battery.
[0017] Preferably, the preparation of the Zn-MOF material comprises the following steps: adding zinc nitrate hexahydrate and 2-methylimidazole to a mixture of methanol and ethanol, stirring and then standing, then filtering and drying to obtain the Zn-MOF material.
[0018] Preferably, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:10-11; and the standing time is 30-50 minutes.
[0019] Preferably, in the mixed solution of methanol and ethanol, the volume ratio of methanol to ethanol is 1:1.
[0020] Preferably, the extrusion temperature of the three-layer co-extrusion is 200-240°C.
[0021] Preferably, the cooling temperature is 80-100° C.; and the pulling speed is 40-80 m / min.
[0022] Preferably, the heat treatment is carried out at a temperature of 110-150° C. and for a time of 10-30 hours.
[0023] Preferably, the temperature of the longitudinal cold stretching is 50-100°C, and the stretching ratio is 1.1-1.5.
[0024] Preferably, the temperature of the longitudinal heat stretching is 140-170° C., and the stretching ratio is 1.7-2.2.
[0025] Preferably, the heat setting temperature is 130-140° C., the stretching ratio is 0.9-1.2, and the time is 1-10 min.
[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) Through the structural design and raw material ratio of the diaphragm, the ion transmission efficiency of the product is improved while ensuring product safety, and the amount of electrolyte required for battery preparation is reduced, which can simultaneously meet the requirements for diaphragm performance in multiple fields such as energy storage and power.
[0027] (2) The lithium-ion battery separator for semi-solid batteries produced by the preparation method of this patent has a puncture performance greater than 350gf, a thickness of 12-20μm, a tensile strength in the MD direction greater than 150MPa, a tensile strength in the TD direction greater than 14MPa, an air permeability of no more than 400s / 100mL, and a battery capacity retention rate of no less than 90% after 100 cycles. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0029] Example 1 The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0030] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 90% PEO and 10% Zn-MOF-derived carbon material.
[0031] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0032] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Zn-MOF material. In a nitrogen atmosphere, the Zn-MOF material was placed in a muffle furnace, heated at a rate of 10°C / min, heated to 900°C and calcined for 4 hours to obtain a Zn-MOF-derived carbon material.
[0033] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0034] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0035] Example 2 The difference from Example 1 is that the raw material of layer A uses 85% PEO and 15% Zn-MOF derived carbon material.
[0036] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0037] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 85% PEO and 15% Zn-MOF-derived carbon material.
[0038] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0039] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Zn-MOF material. In a nitrogen atmosphere, the Zn-MOF material was placed in a muffle furnace, heated at a rate of 10°C / min, heated to 900°C and calcined for 4 hours to obtain a Zn-MOF-derived carbon material.
[0040] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0041] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0042] Example 3 The difference from Example 1 is that the raw material of layer A uses 95% PEO and 5% Zn-MOF derived carbon material.
[0043] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0044] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 95% PEO and 5% Zn-MOF-derived carbon material.
[0045] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0046] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Zn-MOF material. In a nitrogen atmosphere, the Zn-MOF material was placed in a muffle furnace, heated at a rate of 10°C / min, heated to 900°C and calcined for 4 hours to obtain a Zn-MOF-derived carbon material.
[0047] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0048] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0049] Example 4 The difference from Example 1 is that the raw material of layer A uses 85% PEO, 10% Zn-MOF derived carbon material and 5% Zn-MOF material.
[0050] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0051] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 85% PEO, 10% Zn-MOF-derived carbon material and 5% Zn-MOF material.
[0052] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0053] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Zn-MOF material. In a nitrogen atmosphere, the Zn-MOF material was placed in a muffle furnace, heated at a rate of 10°C / min, heated to 900°C and calcined for 4 hours to obtain a Zn-MOF-derived carbon material.
[0054] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0055] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0056] Example 5 The difference from Example 1 is that the Zn-MOF material is calcined at 1200° C. for 3 h to obtain a Zn-MOF derived carbon material.
[0057] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0058] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 90% PEO and 10% Zn-MOF-derived carbon material.
[0059] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0060] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Zn-MOF material. In a nitrogen atmosphere, the Zn-MOF material was placed in a muffle furnace, heated at a rate of 12°C / min, and heated to 1200°C and calcined for 3 hours to obtain a Zn-MOF-derived carbon material.
[0061] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0062] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0063] Example 6 The difference from Example 1 is that the extrusion rate ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 3:7.
[0064] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0065] A layer: The thickness is 2.7 μm (15% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 90% PEO and 10% Zn-MOF-derived carbon material.
[0066] Layer B: thickness is 12.6 μm (thickness is 70% of the total thickness); the raw material of layer B is polypropylene material with low melt index (0.8-1.0 g / 10min).
[0067] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Zn-MOF material. In a nitrogen atmosphere, the Zn-MOF material was placed in a muffle furnace, heated at a rate of 10°C / min, heated to 900°C and calcined for 4 hours to obtain a Zn-MOF-derived carbon material.
[0068] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 3:7, and the extruder temperature is adjusted to 210°C. After melting, the material is filtered, and the material extruded by the first twin-screw extruder is used as the A layer, and the material extruded by the second twin-screw extruder is used as the B layer, and is extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0069] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0070] Comparative Example 1 The difference from Example 1 is that the raw material of layer A is only PEO.
[0071] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0072] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw material of the A layer is PEO.
[0073] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0074] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) The raw material of layer A is put into a first twin-screw extruder; the raw material of layer B is put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the material extruded by the first twin-screw extruder is filtered as the A layer, and the material extruded by the second twin-screw extruder is used as the B layer, and is extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0075] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0076] Comparative Example 2 The difference from Example 1 is that the raw material of layer A uses 90% PEO and 10% Ni-MOF derived carbon material.
[0077] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0078] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 90% PEO and 10% Ni-MOF-derived carbon material.
[0079] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0080] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Nickel nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Ni-MOF material. In a nitrogen atmosphere, the Ni-MOF material was placed in a muffle furnace, heated at a rate of 10°C / min, and heated to 900°C and calcined for 4 hours to obtain Ni-MOF-derived carbon material.
[0081] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0082] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0083] Comparative Example 3 The difference from Example 1 is that the raw material of layer A uses 90% PEO and 10% Co-MOF derived carbon material.
[0084] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0085] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 90% PEO and 10% Co-MOF-derived carbon material.
[0086] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0087] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Cobalt nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Co-MOF material. In a nitrogen atmosphere, the Co-MOF material was placed in a muffle furnace, heated at a rate of 10°C / min, and heated to 900°C for 4 hours to obtain a Co-MOF-derived carbon material.
[0088] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0089] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0090] Comparative Example 4 The difference from Example 1 is that the raw material of layer A uses 90% PEO and 10% Zn-MOF material.
[0091] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0092] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 90% PEO and 10% Zn-MOF material.
[0093] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0094] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water respectively, and then dried and ground to obtain a Zn-MOF material.
[0095] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0096] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0097] Comparative Example 5 The difference from Example 1 is that the raw material of layer A uses 85% PEO, 5% Zn-MOF derived carbon material and 10% Zn-MOF material.
[0098] The composite separator for semi-solid batteries includes an ABA three-layer structure with a total thickness of 18μm.
[0099] A layer: The thickness is 1.8 μm (10% of the total thickness), and the thickness of the upper and lower A layers is the same; in terms of mass percentage, the raw materials of the A layer are 85% PEO, 5% Zn-MOF-derived carbon material and 10% Zn-MOF material.
[0100] Layer B: thickness is 14.4 μm (80% of the total thickness); the raw material of layer B is polypropylene material with a low melt index (0.8-1.0 g / 10min).
[0101] The preparation of the composite diaphragm for the semi-solid battery comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole were added to a mixture of methanol and ethanol (volume ratio of 1:1) in a molar ratio of 1:10, stirred thoroughly and allowed to stand for 30 minutes, then filtered, washed with ethanol and water, dried and ground to obtain Zn-MOF material. In a nitrogen atmosphere, the Zn-MOF material was placed in a muffle furnace, heated at a rate of 10°C / min, heated to 900°C and calcined for 4 hours to obtain a Zn-MOF-derived carbon material.
[0102] (2) The raw materials of layer A are put into a mixing silo in proportion for mixing, and then put into a first twin-screw extruder; the raw materials of layer B are put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder (including the upper and lower A layers) and the second twin-screw extruder is set to 2:8, and the extruder temperature is adjusted to 210°C. After melting, the materials are filtered, and the materials extruded by the first twin-screw extruder are used as the A layer, and the materials extruded by the second twin-screw extruder are used as the B layer, and are extruded through a three-layer die; the melt extruded through the die is cooled at a temperature of 100°C, and is pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet.
[0103] (3) The cast sheet was heat treated at 135°C for 18 h; then the heat treated cast sheet was firstly cold stretched longitudinally at 85°C with a stretching ratio of 1.2, then hot stretched longitudinally at 140°C with a stretching ratio of 2.0, and then heat set at 140°C for 4 min with a heat setting stretching ratio of 0.98, thereby obtaining a composite separator for a semi-solid battery.
[0104] The composite diaphragms prepared in the above examples and comparative examples were cut into A4 size and subjected to various tests. The results are shown in Table 1.
[0105] The test items and methods are as follows: (1) Average thickness: Use a micrometer to measure the thickness of the composite diaphragm at different locations and calculate the average value.
[0106] (1) Tensile strength: The longitudinal and transverse tensile strength of the composite diaphragm was tested using the CTM universal testing machine produced by Xieqiang. Five specimens were tested in each direction and the average value was calculated.
[0107] (2) Puncture strength: The composite diaphragm puncture strength was tested using the Xieqiang CTM universal testing machine. Five specimens were tested and their average value was calculated.
[0108] (3) Air permeability: Use an air permeability tester to test the air permeability of the composite diaphragm. Test 5 samples and calculate the average value.
[0109] (4) Liquid absorption rate: The liquid absorption rate of the composite membrane was tested by weighing method. First, the composite membrane was completely dried and its mass was recorded. Then, the completely dried composite membrane was immersed in electrolyte (prepared by dissolving lithium hexafluorophosphate LiPF6 in a mixed solvent consisting of ethylene carbonate EC, dimethyl carbonate DMC, and ethyl methyl carbonate EMC in a volume ratio of 1:1:1) for 24 hours. After wiping off the surface electrolyte, the weight of the membrane was recorded again. The difference between the two records was the liquid absorption rate of the composite membrane. Five samples were tested and their average value was calculated.
[0110] (5) 100-cycle battery capacity retention test: In an argon environment, the composite diaphragm is placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then an electrolyte (prepared by dissolving lithium hexafluorophosphate LiPF6 in a mixed solvent consisting of ethylene carbonate EC, dimethyl carbonate DMC, and ethyl methyl carbonate EMC in a volume ratio of 1:1:1) is added to assemble a CR2032 button battery. The first test capacity is recorded as the initial capacitance, and it is recorded again after 100 cycles, and the 100-cycle capacity retention rate of the battery is calculated.
[0111] Table 1
[0112] As shown in Table 1, the data of Examples 1-3 show that increasing the proportion of Zn-MOF derived carbon material added to the composite diaphragm improves the capacity retention rate of the battery, but due to the limitation of the internal materials of the battery, continuing to increase the amount of Zn-MOF derived carbon material added will not significantly improve the capacity retention rate of the battery, and the mechanical properties of the diaphragm will be greatly affected. The data of Examples 1 and 5 show that when the calcination temperature of the Zn-MOF material is increased, the obtained Zn-MOF derived carbon material will have structural collapse due to calcination at high temperature for a long time, and the capacity retention rate will be reduced. The data of Examples 1 and 6 show that reducing the thickness of the middle B layer of the composite diaphragm will affect the mechanical related properties of the diaphragm because the polypropylene material plays a mechanical support role. However, the performance data in Examples 1-6 are better than those in Comparative Examples 1-5, indicating that the composite diaphragm obtained within the scope of the present invention can obtain better performance effects.
[0113] In Comparative Example 1, no Zn-MOF derived carbon material was added, and the mechanical properties, wettability, capacity retention rate and other properties of the obtained diaphragm were poor. Compared with Comparative Example 1, Examples 1-5 introduced Zn-MOF materials or Zn-MOF derived carbon materials, which improved the wettability of the overall diaphragm and the liquid absorption rate of the diaphragm. The carbon skeleton structure obtained after the calcination of Zn-MOF further improved the wettability due to defects in the calcination process. In Comparative Examples 2-3, the derived carbon materials prepared using Ni-MOF and Co-MOF still have metal clusters, which cannot achieve Zn vaporization and escape through high-temperature calcination like Zn-MOF materials. Therefore, the stability and wettability are not as good as those of Zn-MOF derived carbon materials, and the battery capacity retention rate will also be reduced.
[0114] The data of Example 2 and Example 4 show that by adding Zn-MOF material to replace part of the Zn-MOF-derived carbon material, the mechanical properties, liquid absorption rate, etc. of the diaphragm will not be significantly reduced, but the Zn-MOF material has a disintegration problem during long-term charging and discharging, so the battery capacity retention rate will be reduced. However, by controlling the amount of Zn-MOF material added within a certain range, a performance effect better than the comparative example can still be obtained, indicating that Zn-MOF material and Zn-MOF-derived carbon material can obtain a better synergistic effect under a certain proportion. Since only Zn-MOF material was added to Comparative Example 4, the capacity retention rate is significantly reduced. Too much Zn-MOF material was added in Comparative Example 5, which also resulted in a significant decrease in the capacity retention rate, but slightly higher than Comparative Example 4.
[0115] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A composite diaphragm for a semi-solid battery, characterized in that: The composite diaphragm includes an ABA three-layer structure obtained by co-extrusion of three layers; the raw material of the B layer includes polypropylene; in terms of mass percentage, the raw material of the A layer is 85-95% PEO, 0-5% Zn-MOF material and the remaining Zn-MOF derived carbon material; the Zn-MOF derived carbon material is obtained by calcining the Zn-MOF material at 900-1200°C in an inert atmosphere for 3-6 hours.
2. The composite separator for a semi-solid battery according to claim 1, characterized in that: In the ABA three-layer structure, the thickness ratio of layer A, layer B and layer A is 10-20%: 60-80%: 10-20%, and the thickness of the upper and lower A layers is the same.
3. The composite separator for a semi-solid battery according to claim 1 or 2, characterized in that: The thickness of the composite membrane is 12-20 μm.
4. The composite separator for a semi-solid battery according to claim 1, characterized in that: The melt index of the polypropylene is 0.8-1.0 g / 10 min.
5. A method for preparing a composite separator for a semi-solid battery according to any one of claims 1 to 4, characterized in that: The steps include: (1) In an inert atmosphere, calcining the Zn-MOF material at 900-1200°C for 3-6 hours to obtain a Zn-MOF-derived carbon material; (2) The raw materials of layer A and layer B are mixed in proportion, and then subjected to three-layer co-extrusion, cooling and pulling to obtain a cast sheet; (3) The cast sheet is subjected to heat treatment, longitudinal cold stretching, longitudinal hot stretching, and heat setting in sequence to obtain a composite separator for a semi-solid battery.
6. The method for preparing a composite separator for a semi-solid battery according to claim 5, characterized in that: The preparation of the Zn-MOF material comprises the following steps: adding zinc nitrate hexahydrate and 2-methylimidazole into a mixed solution of methanol and ethanol, stirring and then standing, filtering and drying to obtain the Zn-MOF material.
7. The method for preparing a composite separator for a semi-solid battery according to claim 6, characterized in that: The molar ratio of the zinc nitrate hexahydrate to 2-methylimidazole is 1:10-11; and the standing time is 30-50 minutes.
8. The method for preparing a composite diaphragm for a semi-solid battery according to claim 5, characterized in that: The extrusion temperature of the three-layer co-extrusion is 200-240°C.
9. The method for preparing a composite separator for a semi-solid battery according to any one of claims 5 to 8, characterized in that: The cooling temperature is 80-100° C.; the pulling speed is 40-80 m / min.
10. The method for preparing a composite separator for a semi-solid battery according to any one of claims 5 to 8, characterized in that: The heat treatment temperature is 110-150° C. and the time is 10-30 hours.
Citation Information
Patent Citations
Polypropylene / polyethylene / polypropylene three-layer co-extruded lithium-ion battery separator and preparation method thereof
CN107331822A
Lithium-sulfur battery functional composite diaphragm and preparation method therefor
CN107681091A
Composite diaphragm for lithium batteries and preparation method of composite diaphragm for lithium batteries
CN108039443A
Separation film for lithium secondary battery having adhesive layer
CN110249447A
Double-coating diaphragm capable of simultaneously inhibiting lithium dendrites and shuttle effect and preparation method thereof
CN111682147A